DESKRIPSI KEPATUHAN PENERAPAN PROTOKOL KESEHATAN P ADA REMAJA DI SMA YOS SUDARSO DOBO KABUPATEN KEPULAUAN ARU - Melanton Wamir; Henry Sudiyanto; Atikah Fatmawati; K3, Mujiadi (MEDICA MAJAPAHIT, 2023)
School institutions was one of the were as of youth activity that should implement health protocols to prevent the spread of COVID-19. Compliance in implementing health protocols was very necessary here, but the phenomenon that occurs in the field was that currently there were still many teenagers who were less concerned with the rules and policies made by the government regarding health protocols. This study aims to determine compliance with the application of health protocols in adolescents at Yos Sudarso Dobo High School, Aru Islands Regency. this study used a descriptive research design. The population was 412 students at Yos Sudarso Dobo High School, Aru Islands Regency. The sampling used was stratified proportional random sampling so that 42 samples were obtained. The research instrument used a questionnaire. Data analysis usrd univariate analysis. The results showed that most of the respondents did not comply in implementing the health protocol, as many as 23 respondents (58%), and the compliant respondents were 19 respondents (45.2%). The results of data analysis show that this non-compliance was caused because there were still many respondents who did not use masks when interacting with other people, do not use 3 ply masks, did not maintain a minimum distance of 1 meter from other people and avoid crowds. The conclusion from the results of this study was that the majority of adolescents in the implementation of health protocols at Yos Sudarso Dobo High School, Aru Islands Regency were non-compliant. The school was expected to work together across sectors between health workers and youth leaders to provide health education to adolescents in order to increase compliance in implementing health protocols because the pandemic was not over yet.